2014
DOI: 10.2340/00015555-1680
|View full text |Cite
|
Sign up to set email alerts
|

Serum Angiopoietin-like Protein 3 Levels: Possible Correlation with Progressive Skin Sclerosis, Digital Ulcers and Pulmonary Vascular Involvement in Patients with Systemic Sclerosis

Abstract: Angiopoietin-like protein 3 (ANGPTL3), which is part of a family of secreted glycoproteins that are structurally similar to angiopoietins, is principally expressed in the liver and is involved in lipid metabolism and angiogenesis. The aim of this study was to determine the clinical significance of serum ANGPTL3 levels, measured with a specific enzyme-linked immunosorbent assay, in patients with systemic sclerosis. Serum ANGPTL3 levels correlated positively with skin score in diffuse cutaneous systemic sclerosi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…The role of fatty acid oxidation in PAH is further emphasized in a study showing that mice lacking the gene for the metabolic enzyme malonyl‐coenzyme A decarboxylase (MCD), an enzyme involved in fatty acid oxidation, do not develop PAH during chronic hypoxia 45 . Studies have shown that serum levels of secreted glycoproteins involved in lipid metabolism and angiogenesis, such as angiopoietin‐like protein 3 (ANGPTL3), are positively correlated with RVSPs and could contribute to PAH in systemic sclerosis 46 . In summary, abnormal cellular metabolism and impaired mitochondrial function could play an important role in the pathogenesis of PAH (Fig.…”
Section: Oxidative Stress and Impaired Mitochondrial Function In The Pathogenesis Of Pah And Associated Rv Failurementioning
confidence: 99%
See 1 more Smart Citation
“…The role of fatty acid oxidation in PAH is further emphasized in a study showing that mice lacking the gene for the metabolic enzyme malonyl‐coenzyme A decarboxylase (MCD), an enzyme involved in fatty acid oxidation, do not develop PAH during chronic hypoxia 45 . Studies have shown that serum levels of secreted glycoproteins involved in lipid metabolism and angiogenesis, such as angiopoietin‐like protein 3 (ANGPTL3), are positively correlated with RVSPs and could contribute to PAH in systemic sclerosis 46 . In summary, abnormal cellular metabolism and impaired mitochondrial function could play an important role in the pathogenesis of PAH (Fig.…”
Section: Oxidative Stress and Impaired Mitochondrial Function In The Pathogenesis Of Pah And Associated Rv Failurementioning
confidence: 99%
“…45 Studies have shown that serum levels of secreted glycoproteins involved in lipid metabolism and angiogenesis, such as angiopoietin-like protein 3 (ANGPTL3), are positively correlated with RVSPs and could contribute to PAH in systemic sclerosis. 46 In summary, abnormal cellular metabolism and impaired mitochondrial function could play an important role in the pathogenesis of PAH (Fig. 2).…”
Section: Oxidative Stress and Impaired Mitochondrial Function In The mentioning
confidence: 99%
“…To date, there are no studies in which the ANGPTL4 level in SSc has been assessed. However, ANGPTL4 and ANGPTL3 share numerous features, and the level of ANGPTL3 has been found to be increased in patients with SSc, and associated with the prevalence of digital ulcers, suggesting the involvement of ANGPTL3 in the pathogenesis of SSc-associated microangiopathy (30). In this regard, clarifying the role of ANGPTLs in SSc may lead to further understanding of the complex SSc pathogenesis.…”
Section: Hypoxia In Systemic Sclerosis: the Hif Pathway And Its Dysrementioning
confidence: 99%